Pengaruh Pendidikan Kesehatan Dengan Menggunakan Media AudiovisualTerhadap Pengetahuan Remaja DalamMencegah Perilaku Kekerasan Seksual DI SMA N 2 KotaGorontalo - Elisa Putri Luawo; Firma Wati (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2026)
The Effect of Health Education Using Audiovisual Media on Adolescents' Knowledge in Preventing Sexual Violence Behavior in SMA Negeri 2 Gorontalo City. Supervised by Firmawati as the chairperson and Andi Akifa Sudirman as a member. Adolescents are an age group vulnerable to risky behavior, including premarital sexual behavior that is at risk of experiencing sexual violence, this can be handled by providing health education to improve adolescents' knowledge and attitudes regarding sexual violence behavior, one of which is by using audiovisual. The purpose of this study was to determine whether there was an effect of health education using audiovisual media on adolescents' knowledge in preventing sexual violence behavior in SMA Negeri 2 Gorontalo City. The quantitative research design used a quasi-experimental method with a one-group pre-post test approach, the population of all female students of SMA 2 Gorontalo City was 626 people, the number of samples was 17 people using purposive sampling techniques and the data were analyzed using the Wilcoxon statistical test. The results of the study showed that the average score of the level of knowledge before was 5.71 with a standard deviation of 2.024 and the average score of the level of knowledge after was 8.00 with a standard deviation of 1.458. Then, the results of the Wilcoxon analysis obtained a p-value of 0.000 (<α 0.05). It was concluded that there was an influence of health education using audiovisual media on adolescents' knowledge in preventing sexual violence behavior. Therefore, schools can provide health education regarding the prevention of sexual violence in the teaching and learning process because currently there are many cases of sexual violence, especially among adolescents. Keywords: Audiovisual, Sexual Violence Behavior, Adolescents